Melatonin menurunkan berat badan tetapi tidak menurunkan kadar TNF-Î± pada tikus wistar jantan yang diberi minyak jelantah selama 28 hari - Novianti, Anugrah; Dharmana, Edi; Widyastiti, Nyoman Suci (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Backgound: Non Alcoholic Fatty Liver Disease (NAFLD) occurs when the intake and free fatty acid synthesis occurs more frequently than its oxidation and resecretion in the blood. Melatonin is a powerful antioxidant that can boost the synthesis of endogenous antioxidants in the body, suppress the inflammatory response and inhibit the formation of steatosis.Objective: To analyze the effect of melatonin supplementation in reducing body weight andTNF-Î± levels in male Wistar rats were fed by waste cooking oil.Methods: True experimental studyusing post-test only control group design. This study was done on 18 male wistar rats were divided into 3 groups : the positive control group (P0) was administrated waste cooking oil, the treated group 1 (P1) was administrated waste cooking oil and 5mg/kgBW melatonin, and the treated group 2 (P2) was administrated waste cooking oil and 10mg/kgBW melatonin for 28 days.Data analysis using One Way ANOVA test and followed by Tukey test to determine the most effective dose of melatonin.Results: There was significant difference in body weightbetween P2group and K0 group (p=0,019) with the mean body weight difference was 19,167g lower than K0 group. There was no difference in TNF-Î± levels between the three groups (p=0,155). Conclusion: Melatonin dose of 10mg/kgBWloses body weight male Wistar rats have given by waste cooking oil for 28 days, but does not reduce TNF-Î± levels.